2017
DOI: 10.1049/mnl.2016.0819
|View full text |Cite
|
Sign up to set email alerts
|

Controllable preparation and photocatalytic activity of highly ordered ZnO nanoarrays

Abstract: Well-aligned ZnO nanotubular arrays (NTs) and nano rod-like arrays (NRs) were controllably fabricated on glass substrates through a facile hydrothermal method, and the prepared ZnO nanoarrays could be easily retrieved in the photodegradation of organic pollutants because ZnO is "growing" on the substrates. The morphology of ZnO nanoarrays could be governed by the cooling process and reaction time during the preparation. ZnO NTs tend to be formed by natural cooling, while ZnO NRs are apt to be constructed by su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Therefore, the effective removal of the bacteria debris is the key to the persistent and fast bacteria killing. Semiconductors have been well studied for organic pollutant degradation (Iqbal et al, 2014;Rajamanickam and Shanthi, 2016;Xiang et al, 2012), where nanoarrays were found to exhibit better catalytic performance due to the multiple light scattering and increase in optical path length enabled by the columnar hierarchical structures (Gao et al, 2015;Iqbal et al, 2014;Kong et al, 2017;Park et al, 2013). Although TiO 2 nanosisal structures has been proved feasible in the complete removal of bacteria debris after several hours (Meng et al, 2015), it has not been explored yet how the nanostructured semiconductor surface can endow the physical bactericidal surfaces with self-cleaning features for ultrafast bacteria inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effective removal of the bacteria debris is the key to the persistent and fast bacteria killing. Semiconductors have been well studied for organic pollutant degradation (Iqbal et al, 2014;Rajamanickam and Shanthi, 2016;Xiang et al, 2012), where nanoarrays were found to exhibit better catalytic performance due to the multiple light scattering and increase in optical path length enabled by the columnar hierarchical structures (Gao et al, 2015;Iqbal et al, 2014;Kong et al, 2017;Park et al, 2013). Although TiO 2 nanosisal structures has been proved feasible in the complete removal of bacteria debris after several hours (Meng et al, 2015), it has not been explored yet how the nanostructured semiconductor surface can endow the physical bactericidal surfaces with self-cleaning features for ultrafast bacteria inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…As an important semiconductor with a direct wide bandgap of 3.37 and 60 meV of exciton binding energy at room temperature [4,5], zinc oxide (ZnO) has wide application in electronics, spintronics, PH and gas sensors, photocatalyst, biosensors, transparent electrodes [6][7][8], and so on. It is well known that excellent properties of materials are obviously dependent on the morphology and structures.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the random distributed PCP complexes, the formation of close and ordered arrangement of PCP structures as well as the controlled uniform distance between PCP complexes and gold microplates facilitate the directional flow of generated electrons in photoelectrochemical system. Moreover, the formation of close packed and ordered arrangements can enhance the visible-light harvesting ability for capturing more light and improve the lifetime of hot electrons to let more electrons arrive at Pt electrode, which results in enhancement of photoelectrochemical activity too . Consequently, the photoelectrochemical performances of the designed system are remarkably improved due to the decreased loss of electrons decreased.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the formation of close packed and ordered arrangements can enhance the visible-light harvesting ability for capturing more light and improve the lifetime of hot electrons to let more electrons arrive at Pt electrode, which results in enhancement of photoelectrochemical activity too. 52 Consequently, the photoelectrochemical performances of the designed system are remarkably improved due to the decreased loss of electrons decreased. In other words, light-harvesting ability and the efficiency of separation, migration, and transfer of electron− hole pairs in linked Au-PCP photoelectrochemical systems are enhanced as the formation of self-assembled arrangements of PCP complexes and the well-controlled distance with plasmonic gold microplates.…”
mentioning
confidence: 99%